Rats (Rattus norvegicus) find occupancy of a restraint tube rewarding. Issue 3 (1st April 2020) - Hachiga, Yosuke; Silberberg, Alan; Slotnick, Burton; Gomez, Maria
Abstract : Two experiments evaluated whether rats' occupancy of a restraint tube is reinforcing. In Experiment 1, each rat in the 0‐min group moved freely in a chamber where a wall blocked access to a restraint tube. After 10 min the wall was removed, permitting 15 min of chamber access and tube entry. The other 2 groups were locked in the tube for 10 and 20 min respectively before release into the chamber for 15 min. Across sessions, rats locked up for 10 and 20 min entered the tube more frequently than rats in the 0‐min group, and during the first 2 sessions rats in the 20‐min group stayed in the tube longer than the other groups. Over sessions this difference disappeared. However, for all groups and sessions the mean percentage of session time in the tube exceeded chance expectations. This result suggests tube occupation was reinforcing. In Experiment 2's Phase 1, rats could enter an open tube. On exiting, the tube door closed. A lever press opened the door for the rest of the 1‐hr session. In Phase 2, these rats were locked in the tube for 10 min before the door opened. Upon exiting, the door closed. As in Phase 1, a lever press opened the door for the rest of the session. The latency between pressing and tube entry decreased over sessions, indicating that tube entry reinforced lever pressing. These results are difficult to reconcile with accounts of rat empathy based on the thesis that tube restraint distresses occupants.